Pendidikan Kewarganegaraan Sebagai Alat Pencegah Pelanggaran HAM: Evaluasi Program Pendidikan di Indonesia - Alda Azzahra Fadila; Putri Hermaisya Harahap; Sapna Maulini Hasibuan; Salsanabila Salsanabila; Marisa Kemala Rozi; Riyan Hidayat Meliala (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Human rights are a fundamental problem in every country, especially in developing countries like Indonesia. As a democratic country, Indonesia must pay attention to this. Human rights must be taught in schools to every student. This research aims to find out whether citizenship education can be used as a tool to prevent human rights violations and how it affects the evaluation of education programs in Indonesia. By using this method, it is hoped that everyone will know their rights and obligations well. Citizenship education can be an important means to achieve this goal, because citizenship education is one of the learning tools that talks about human rights and is studied in all schools. The method used in this research is literature review, the literature review aims to make an analysis and synthesis of existing knowledge related to the topic to be researched. The research results show that the quality of education services is still low due to inadequate support for facilities and teaching staff throughout Indonesia, especially in remote areas. This results in the number of students dropping out of school remaining high, so that many Indonesian students are unable to continue their education to a higher level.